A Visão do Professor sobre Jogos Digitais no Ensino da Matemática para alunos com Deficiência Intelectual: Estado da arte Teacher´s view about digital games in Mathematics Education for students with intellectual disabilities: State of art - Silva, Simone dos Santos Venturelli Antunes; Ferraz, Denise Pereira de Alcantara (Educação Matemática Pesquisa Revista do Programa de Estudos Pós-Graduados em Educação Matemática, 2019)
O presente artigo decorre de pesquisa cuja temática é o uso de jogos digitais no ensino de matemática a alunos com Deficiência Intelectual (DI). O objeto deste artigo é responder à seguinte questão: o que foi produzido no período de 2009 a 2018 sobre o ensino da matemática mediado por jogos digitais para alunos com DI? O recorte tem como foco a visão do professor. Para isso, realizou-se um estudo do estado da arte por meio de buscas no Google Acadêmico, nos bancos de dados da CAPES e Academia.edu. Percebe-se uma tendência por parte dos professores em reportar falta de capacitação para lidar com os computadores, além de considerarem que o uso de jogos digitais com objetivos didáticos traz benefícios ao aprendizado e à autonomia do aluno com DI. Conclui-se que este é um campo fértil para a realização de novas pesquisas. This study is part of a doctoral research and investigates the knowledge of the teacher in a training action guided by and for the investigative approach in mathematics classes. The cut considers the analysis of results obtained in practice with teaching cases as a pedagogical tool in teacher training. In the methodological perspective of the research with narratives, the proposal is presented, detailing the objectives and characteristics of the teaching cases, describing its development and presenting reflections and analyzes in light of the problematic: What understandings about the investigative approach in mathematics classes are produced by teachers through training in case studies? The results point to the potential of teaching cases in the understanding of the investigative approach by the teachers in formation, since the analysis indicates reflections on: investigative task, mathematical activity and communication as dialogue, defined as elements that characterize the investigative approach.